RAD51 foci as a functional biomarker of homologous recombination repair and PARP inhibitor resistance in germline BRCA-mutated breast cancer. (4th April 2018) - Cruz, C; Castroviejo-Bermejo, M; Gutiérrez-Enríquez, S; Llop-Guevara, A; Ibrahim, Y H; Gris-Oliver, A; Bonache, S; Morancho, B; Bruna, A; Rueda, O M; Lai, Z; Polanska, U M; et al.
Abstract: Background: BRCA1 and BRCA2 (BRCA1/2) -deficient tumors display impaired homologous recombination repair (HRR) and enhanced sensitivity to DNA damaging agents or to poly(ADP-ribose) polymerase (PARP) inhibitors (PARPi). Their efficacy in germline BRCA1/2 (gBRCA1/2)-mutated metastatic breast cancers has been recently confirmed in clinical trials. Numerous mechanisms of PARPi resistance have been described, whose clinical relevance in gBRCA-mutated breast cancer is unknown. This highlights the need to identify functional biomarkers to better predict PARPi sensitivity. Patients and methods: We investigated the in vivo mechanisms of PARPi resistance in gBRCA1 patient-derived tumor xenografts (PDXs) exhibiting differential response to PARPi. Analysis included exome sequencing and immunostaining of DNA damage response proteins to functionally evaluate HRR. Findings were validated in a retrospective sample set from gBRCA1/2-cancer patients treated with PARPi. Results: RAD51 nuclear foci, a surrogate marker of HRR functionality, were the only common feature in PDX and patient samples with primary or acquired PARPi resistance. Consistently, low RAD51 was associated with objective response to PARPi. Evaluation of the RAD51 biomarker in untreated tumors was feasible due to endogenous DNA damage. In PARPi-resistant gBRCA1 PDXs, genetic analysis found no in-frame secondary mutations, but BRCA1 hypomorphic proteins in 60% of the models, TP53BP1 -loss in 20% and RAD51 -amplification in one sample, none mutually exclusive. Conversely, one of three PARPi-resistant gBRCA2 tumors displayed BRCA2 restoration by exome sequencing. In PDXs, PARPi resistance could be reverted upon combination of a PARPi with an ataxia-telangiectasia mutated (ATM) inhibitor. Conclusion: Detection of RAD51 foci in gBRCA tumors correlates with PARPi resistance regardless of the underlying mechanism restoring HRR function. This is a promising biomarker to be used in the clinic to better select patients for PARPi therapy. Our study also supports the clinical development of PARPi combinations such as those with ATM inhibitors.